THE EFFECT OF RECRUITMENT AND JOB PLACEMENT ON WORK ACHIEVEMENT AT PT. BANK TABUNGAN NEGARA (PESERO) TBK KCP SIBOLGA - Yenni Sofiana Tambunan; Nelly Azwarni Sinaga; Sinta Veronika Hutabarat (Jurnal Ekonomi, 2023)
This study entitled "The effect of recruitment and placement on employee performance at PT. Bank Tabungan Negara (Pesero) Tbk KCP Sibolga. The purpose of this study was to determine the effect of recruitment and placement on employee performance at PT. Bank Tabungan Negara (Pesero) Tbk KCP Sibolga. The population as well as the sample in this study were all employees at PT. Bank Tabungan Negara (Pesero) Tbk KCP Sibolga, which has a total of 22 employees. The partial results of the hypothesis test show that recruitment has a positive and significant effect on employee performance at PT. Bank Tabungan Negara (Pesero) Tbk KCP Sibolga. Branch with proven t count 2.967 > t table of 1.99254 and probability value 0.004 < α 0.05. Placement has a significant effect on performance because t count is 7.751 > 1.99254 and the probability value is 0.000 <α 0.05. Simultaneously hypothesis testing shows that recruitment and placement have a positive and significant effect on employee performance at PT. Bank Tabungan Negara (Pesero) Tbk KCP Sibolga Branch indicated by F count 44.705 > F table 3.12 and probability value 0.000 < α 0.05